Life Cycle Assessment (LCA) of Natural Fiber Reinforced Polymer Composites for Automotive Interior Panels: A Comparative Study vs. Glass Fiber Composites - Fauzi Ibrahim (Fakultas Teknik Universitas Malahayati, 2026)
The growing demand for lightweight and sustainable vehicles is accelerating the adoption of fiber reinforced polymer composites, including natural fiber reinforced polymer (NFRP) systems for interior components. However, environmental benefits are highly dependent on resin selection, manufacturing route, transport distances, and end of life scenarios. This study presents a cradle to grave Life Cycle Assessment (LCA) comparing NFRP and conventional glass fiber reinforced polymer (GFRP) for an automotive interior panel application. A functional unit is defined as one interior panel meeting equivalent stiffness and service life requirements, enabling fair comparison between materials with different fiber density and specific mechanical performance. Life cycle inventory data are compiled from peer reviewed literature and established LCA databases, covering raw material extraction (natural fibers and glass fibers), polymer matrix production, compounding and forming processes, use phase considerations (mass related fuel/energy penalties where applicable), and end of life scenarios including landfill, incineration with energy recovery, and emerging recycling pathways. Environmental impacts are quantified using midpoint indicators (e.g., global warming potential, cumulative energy demand, acidification, eutrophication, and human toxicity), and uncertainty is addressed via sensitivity analysis on key parameters such as fiber content, resin type (petro based vs. bio based), regional electricity mix, and transportation assumptions. The results are expected to identify dominant “hotspots” across the value chain and to clarify conditions under which NFRP offers measurable reductions in greenhouse gas emissions and energy demand relative to GFRP, while also highlighting trade offs related to land use, eutrophication, and end of life emissions. The findings provide design relevant guidance for material selection and process optimization toward lower impact composite interior parts aligned with circular economy strategies.